Experimental Investigation on Effect of Tool Crater Wear and Surface Roughness in TiN Coated WC Tool While Machining Martensitic Stainless Steel - Maniraj Jaganathan; Selladurai Velappan; Sivashanmugam Nallathambhi; Vendan Subbiah Arungalai; Mathew Jacob (High Temperature Materials and Processes, 2011)
Manufacturing process is significantly altered by tool wear and this factor creates intricate issues that form a hindrance in attaining manufacturing automation. The other vital parameters determining the tool life are the dimensional accuracy and surface roughness of the workparts. In this research work, an attempt is being made to conduct machining studies on martensitic stainless steel AISI410 to analyze the effect of crater wear and surface roughness in TiN coated WC tool. The crater wear and surface roughness values are initially recorded. The recorded data are used as input in the ANOVA plinth and subsequently used for developing mathematical tool wear models using multiple regression analysis (MRA). The results from ANOVA reveal that the cutting speed influences the surface roughness more significantly than feed rate and depth of cut. Further, it is emphasized that, the crater wear is affected more by feed rate as compared to the cutting speed. Consequently, the metallographic studies using scanning electron microscope (SEM) are conducted based on which the effects of crater wear on the TiN coated WC cutting tool are plotted and analyzed.